Strategi Pengembangan Kawasan Wisata Pantai Lombang Kabupaten Sumenep - Mohammad Zainul Arief (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Sumenep Regency has cultural diversity, which is supported by a culture of social life that is different from other districts in Madura. In accordance with government policy in developing tourism, especially in Sumenep Regency, it is necessary to have a guideline for a directed and integrated development plan. Tourist objects that are interesting to visit besides being good attractions also need an orderly and neat arrangement, especially from a physical point of view. In addition, the need for tour packages that are supported by travel agencies, travel agent services, and tour guides. In this study "Strategy for Development of the Lombang Beach Tourism Area, Sumenep Regency" uses SWOT ( Strength , Weakness, Opportunity and Threat ) analysis as an effort to solve problems using a quantitative approach with the type of research in the form of case studies. The Lombang Beach tourism development strategy is seen from the internal factors which are still dominant in having weaknesses in Lombang beach tourism objects, so the stability strategy is the current choice, namely reducing the weak factors gradually according to the existing priority criteria so that the weaknesses disappear and turn into strength. While the internal factors that become strengths must be maintained.